HEALTH AS A KEY TOPIC IN FOREIGN LANGUAGE TEACHING: AN ANALYSIS OF SELECTED TEXTBOOKS (PALIMPSEST / ПАЛИМПСЕСТ, 2026)
Health and illness are universal aspects of human life and therefore play a crucial role in foreign language learning. In recent years, the demand for German language courses by medical professionals has increased, highlighting the need for a systematic integration of health-related topics in teaching materials. This paper examines selected German as a Foreign Language (DaF) textbooks – Menschen (A1–B1), Motive (A1–A2), Momente (A1–B1), and Sicher! (B2–C1) – with regard to the representation of health. The analysis is based on three dimensions: lexical progression, task design, and communicative competence. Findings show a clear progression from basic vocabulary and routine dialogues at beginner levels to complex discussions on psychosomatic and societal health issues at advanced stages. Nevertheless, inconsistencies remain: while general communicative needs are addressed, the specific requirements of medical professionals are often overlooked. The study argues for a systematic and practice-oriented integration of health topics in DaF textbooks to better reflect both social change and professional demands. Such an approach would enhance learner motivation, ensure continuity across proficiency levels, and strengthen the connection between everyday communication and professional discourse.
Keywords: German as a foreign language (DaF); textbook analysis; health communication; language pedagogy; medical vocabulary.